1997
DOI: 10.1023/a:1008212826956
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment prognostic factors for survival in small-cell lung cancer: A new prognostic index and validation of three known prognostic indices on 341 patients

Abstract: A new prognostic index is proposed allowing identification of three different PG. The feasibility of three known prognostic models was validated and demonstrated. Variables other than disease extent or PS (albumin or LDH) should be taken into account in designing future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 26 publications
5
51
1
4
Order By: Relevance
“…8 Hyperglycemia, defined as a random baseline serum glucose level Ͼ 110 mg/dL, also was found to have a significant effect on survival in patients with small cell lung carcinoma. 9 Furthermore, improved glycemic control may improve outcome in patients with malignancy because it has been shown to decrease the incidence of microvascular and, most likely, macrovascular complications in patients with noninsulindependent diabetes mellitus. 10 Strict blood glucose control (Յ110 mg/dL) with intensive insulin therapy also has been shown to reduce morbidity and mortality among critically ill patients in a surgical intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…8 Hyperglycemia, defined as a random baseline serum glucose level Ͼ 110 mg/dL, also was found to have a significant effect on survival in patients with small cell lung carcinoma. 9 Furthermore, improved glycemic control may improve outcome in patients with malignancy because it has been shown to decrease the incidence of microvascular and, most likely, macrovascular complications in patients with noninsulindependent diabetes mellitus. 10 Strict blood glucose control (Յ110 mg/dL) with intensive insulin therapy also has been shown to reduce morbidity and mortality among critically ill patients in a surgical intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…In a study including 341 patients with NSCLC in 1997, Maestu et al (1997) compared three prognostic scoring systems (Royal Marsden Model, London Group Scoring System, and Manchester Scoring System). The authors suggested that albumin and LDH levels might be used in the risk scoring in further studies.…”
Section: 5971 Serum Albumin As a Prognostic Factor With Stage Iiib Nmentioning
confidence: 99%
“…In addition, the number and localization of metastatic lesions and the impact of these lesions on hepatic synthesis were not discussed in these studies. However, hepatic metastasis-related hepatic dysfunction is a well-known cause of hypoalbuminemia (Maestu et al, 1997;Matsunuma et al, 2014).…”
Section: 5971 Serum Albumin As a Prognostic Factor With Stage Iiib Nmentioning
confidence: 99%
See 2 more Smart Citations